The State of Emergency Medical Services in Sub-Saharan Africa - World Bank (Washington, DC: World Bank, 2021)
Health system investments in sub-Saharan Africa (SSA) have historically focused on primary health care to address the high rates of communicable diseases. However, with increasing rates of road trauma along with other life-threatening conditions such as non-communicable diseaseslike cardiac arrest and stroke that require urgent medical attention, many countries must now also look to develop functional Emergency Medical Services (EMS). Providing efficient and effective post-crash care and pre-hospital treatment for injuries, hemorrhage, and other medical and obstetrical emergencies under normal operating conditions become even more critical during disasters or conflict situations. They should also be made a priority due to the increasing morbidity and mortality from medical, surgical and obstetrical emergencies. According to World Health Organization (WHO), Road Traffic Accidents (RTAs) are currently the 8th leading cause of death globally and the 10th leading cause in SSA, resulting in more than 1.4 million deaths per year worldwide in 2016 and 284,000 in SSA. Road injuries do not strike the population equally, and some groups are more vulnerable than others. Globally, RTAs are the leading cause of death for children, adolescents, and young adults aged 5-29 years, and yet have been long neglected in the health agenda for this group. Additionally, more than half of all road traffic deaths are among vulnerable road users including pedestrians, cyclists and motorcyclists. Differences are noticeable between regions: while pedestrians and cyclists represent 26 percent of all deaths worldwide, they represent 44 percent of deaths in Africa. More generally, Africa is the continent with the highest rate of road traffic deaths with 26.6 deaths per 100,000 population in 2016, compared to 18.2 worldwide. It is now estimated that by 2030 the numberof RTA deaths could conceivably increase by 30 percent to 1.85 million fatalities annually, making it the 7th leading cause of death globally. Unfortunately, the RTA death rate in SSA is 25 percent higher than the global average (2015) and it is projected to increase a further 72 percent by 2030 to 38 fatalities per 100,000 population. For SSA, the challenge is even more pressing - if RTAs were to double to 514,000 annually, they would potentially become the 6th leading cause of death by 2030 - making RTAs responsible for more deaths than pre-term birth complications or malaria (ranked 7th and 8th, respectively).